Die Interaktion zwischen Dirigent:in und Musiker:innen in Orchesterproben: Mehrsprachige und multimodale Interaktionsmuster zwischen Worten und Tönen, Händen und Füßen - Messner, Monika (Linguistik – Impulse & Tendenzen, 2023)
This study examines the multilingual and multimodal practices employed by conductors and musicians to communicate and interact with each other during rehearsals of French and Italian symphony orchestras.